Adsorption of Brilliant Yellow onto Sepiolite: Evaluation of Thermodynamics and Kinetics and the Application of Nonlinear Isotherm Models. Issue 12 (1st December 2016) - Tekin, Nalan; Bayrak, Mine Aylin; Can, Emine
Abstract : We studied the adsorption of Brilliant Yellow ( BY ) from aqueous solutions onto sepiolite and determined the adsorption equilibrium isotherms. We applied pseudo-first-order and pseudo-second-order kinetic models; the adsorption of BY onto sepiolite was best described by the pseudo-second-order kinetic model. The experimental data obtained at different temperatures were analyzed using various isotherm models; the Koble–Corrigan isotherm model provided the best fits for the BY adsorption data at all temperatures. The thermodynamic parameters of the BY adsorption onto sepiolite indicated that the adsorption process is spontaneous and exothermic in nature. GRAPHICAL ABSTRACT: